Methamphetamine consumption and life-threatening abdominal complications: A case report. Issue 18 (May 2018) - Zou, Xiaojing; Huang, Haiyan; Yang, Le; Liu, Hong; Li, Yongfeng; Xia, Qin; Yuan, Shiying; Yao, Shanglong
Abstract: Rationale: Methamphetamine (METH) abuse is increasing rapidly all over the world and becoming a significant public health concern in China. However, abdominal complications secondary to METH abuse are usually overlooked. We describe an unusual case of gangrenous cholecystitis and small intestinal ischemia due to METH abuse. Patient concerns: In this report, a 44-year-old male patient with abdominal pain and hematochezia has a history of crystal meth abuse. Diagnosis: The patient was diagnosed as septic shock, paralytic ileus, gangrenous cholecystitis, and small intestinal ischemia due to METH abuse based on computed tomography (CT) scan, endoscopy examination, laparotomy, and pathology. Interventions: Antishock treatment, broad-spectrum antibiotics, and exploratory laparotomy were given. Outcomes: The patient survived. Six months later, he tolerated oral intake and stopped using crystal METH. Lessons: Visceral ischemia should be considered if an adult patient with a history of METH abuse is accompanied by abdominal pain and hematochezia.